Oxygen consumption of the heart during horse riding - Athanasiou, A. (SVOA Orthopaedics, 2022)
Horse riding has three disciplines: show jumping, dressage and endurance. (Singapore Sports Council, 2020) During jumping the rider demonstrates his/her ability to command the horse to jump over obstacles. In dressage, the rider needs to accurately control the horse and perform a series of exercises. During endurance, the rider has to guide the horse through artificial and natural obstacles. There are three different horse gaits: walk, trot and canter (British Dressage, 2021). The walk is a marching pace with a 4 time tempo. The trot is a two beat rhythmic pace, with four different types. Canter is a three beat pace with four different types, similar to trot. The aim of the study is to investigate the oxygen consumption of the riders during the three different disciplines and compare VO2 and heart rate during the different disciplines. This knowledge will assist instructors and riders while planning training sessions and preparing for competition.